(untitled) (Damascus University Journal for engineering sciences, 2022)
Background and aim: The correlation between age groups, body mass index and cancer grade with serological concentrations of immunological biomarkers (interleukin IL-1B, IL-6, IL-10 and INF-ɤ) among females with breast cancer was carried out in this study. Methods: The total number of breast cancer patients involved in this study are (80) individual were taken from Basrah oncology center in Basrah province, the age of patients range from 27-76 yrs and (80) individuals considered as control group after they were checked and confirmed to be free from any chest or any other health problems. Results: The levels of interleukin IL-1B, IL-6, IL-10 and INF-gamma (pg/ml) were determined among patients with breast cancer and control groups in various age groups, stages of breast cancer and various body mass indices . Conclusion: there are statistical correlation between various clinical factors and various stages of breast cancer